Full-length genome analysis of Čalovo strains of Batai orthobunyavirus (Bunyamwera serogroup): implications to taxonomy - Dufkova, Lucie; Pachler, Karin; Kilian, Patrik; Chrudimský, Tomáš; Danielová, Vlasta; Růžek, Daniel; Nowotny, Norbert (Infection, genetics and evolution, 2014)
Batai virus (BATV) is a poorly studied arthropod-borne virus belonging to the genus Orthobunyavirus (Bunyamwera serogroup) within the family Bunyaviridae. It has been associated with human influenza-like febrile illness in several Asian, African, and European countries. Čalovo virus (CVOV), isolated in 1960 in Slovakia, has been classified as BATV based on high antigenic similarity, and since then both CVOV and BATV were used as synonyms. In order to fully clarify the phylogenetic relationships between CVOV, BATV, and other members of the Bunyamwera serogroup, we performed whole genome sequencing of four CVOV strains isolated in Europe and phylogenetic analyses of all related viruses. The nucleocapsid protein, encoded by the S genomic segment, contains 233 amino acids, 60 of which, putatively critical for protein function, are conserved. Within the CVOV polyprotein encoded by the M genomic segment, putative cleavage sites, N-glycosylation sites, and seven transmembrane regions were identified. The RNA-dependent RNA polymerase, encoded by the L genome segment, exhibits conservation of the three regions known to be conserved among bunyavirus and arenavirus L proteins. Phylogenetic analyses of all three genomic segments of selected orthobunyaviruses clearly revealed that European and Asian/African strains of BATV are phylogenetically different and form two distinct lineages, indicating the existence of two different genotypes of BATV, tentatively named European genotype (with CVOV as a type strain) and Afro-Asian genotype (with BATV as a type strain) of BATV.
Keywords: séroskupina; Genome, Viral; sekvenční homologie aminokyselin; Sequence Homology, Amino Acid; Viral Proteins; genom virový; RNA, Viral; Genomics; lidé; Molecular Sequence Data; Evolution, Molecular; molekulární evoluce; RNA virová; Phylogeny; molekulární sekvence - údaje; Orthobunyavirus; sekvenční homologie nukleových kyselin; Sequence Homology, Nucleic Acid; virové proteiny; Sequence Analysis, DNA; sekvenční analýza DNA; fylogeneze; Serogroup; genomika; Humans